The development of a portable optical system for telemonitoring of skin blood oxygen level - Hong Xuan, Mars Wai; Ngu, Xavier; Huong, Audrey (Penerbit Uthm, 2019)
Oxygen is one of the keys parameters required for tissues metabolism to ensure life sustainability. Without it, human’s health would suffer and eventually result in fatal. Cells consume oxygen to break down sugar to produce adenosine triphosphate (ATP) during cellular respiration [1]. ATPs are the main source of energy for metabolic functions [2] and every cell in the body, especially muscles cell, for its ability to store and use energy; muscle would not contract or relax without ATP. Cell is not able to function well under the condition of low oxygen level, thus it would lead to hypoxemia. If left untreated, severe hypoxemia can be fatal [3].